EP 62. Functional connectivity and characterization of subregions within left intraparietal sulcus. Issue 9 (September 2016) - Cieslik, E.; Müller, V.; Grefkes, C.; Laird, A.; Fox, P.; Eickhoff, S.
Abstract : Introduction: The intraparietal sulcus (IPS), located at the intersection of visual, auditory and somatosensory association cortices, has been associated with the multi-modal spatial representation of the external world (Grefkes, 2005 ). Moreover, the IPS has been reported to be involved in higher executive functions such as working memory or cognitive flexibility. In a previous co-activation based parcellation study we could identify five functional subregions within the left IPS (Cieslik, 2013 ). To characterize the individual clusters we here used meta-analytic connectivity modelling (MACM) for investigation of each cluster's functional connectivity (FC) as well as functional profiling using the BrainMap database (brainmap ). Methods: MACM-FC of the IPS' subregions was investigated by first identifying those experiments in the BrainMap database activating the respective cluster. Performing a meta-analysis over these experiments revealed those regions showing significant co-activation with the cluster. To identify regions in the brain revealing consistent FC with all five IPS subregions, we performed a conjunction analysis across the FC results of the individual clusters. In a next step, specific co-activation patterns for all five clusters were derived by performing a conjunction analysis across the differences between a given cluster and the four other ones. Moreover, forward and reverse inference was performed using the 'Paradigm Class' categories of the BrainMap database to characterize differentiable functions of individual clusters. Results: The present study reveals consistent FC of all individual subclusters with a bilateral fronto-parietal network that has been associated with multiple demand processes [6, 7]. Moreover, when looking at differential FC and behavioural characterization of individual clusters it was found that cluster C1 and C4 - located in the more posterior-lateral fundus of the IPS - were strongly associated with paradigms requiring higher cognitive control, such as the Wisconsin Card Sorting Test and n-back task, respectively. These clusters furthermore showed specific FC with regions in the prefrontal cortex, such as the inferior frontal junction for C1 and the dorsolateral prefrontal cortex and middle frontal gyrus for C4. In contrast, more anterior (C3) and more dorsal – C2 and C5 – clusters were stronger associated with visuo-motor paradigms. C2 showed specific FC with the precentral gyrus while C3 and C5 showed specific FC only with the respective contralateral homotopic region. Conclusion: These results hence provide evidence for an anterior-posterior gradient in the left IPS, with more anterior and dorsal clusters strongly involved in linking perception to action and more posterior lateral clusters featuring higher cognitive functions, such as working memory and cognitive flexibility.